Penerapan Metode Double Moving Average Untuk Memprediksi Penjualan Tiket Kereta Api - Demonius Sarumaha (Explorer, 2021)
Prediction (Forecasting) is carried out by almost everyone, be it the government, businessmen, or ordinary people. The predicted problems vary, such as the forecast of rainfall, the possible winner of the presidential election, the score of the match, the number of sales or the inflation rate. The Double Moving Avarage method is a method that can be used to solve anything related to the forecast series and situation. It should be understood that Double Moving Avarage is very good at forecasting. The Double Moving Avarage method only uses one variable as a basis for making predictions so that in this model there is no term independent variable used to predict the value of the dependent variable. This model uses past and present values ​​as the basis for prediction. Therefore, it is very appropriate to use in predicting. Increased number of ticket sales at PT. Kereta Api Indonesia (Persero) Medan has always been a discussion that has never been overlooked by company leaders, therefore prediction or forecasting is very useful to see pictures of the future so that the leadership can anticipate it with future events. For example, a company can estimate the number of passengers during the Eid al-Fitr season in 2019.